Disruption of OVOL2 Distal Regulatory Elements as a Possible Mechanism Implicated in Corneal Endothelial Dystrophy - Dudakova, Lubica; Noskova, Lenka; Kmoch, Stanislav; Filipec, Martin; Filous, Ales; Davidson, Alice E; Toulis, Vasileios; Jedlickova, Jana; Skalicka, Pavlina; Hartmannova, Hana; Stranecky, Viktor; Drabova, Jana; et al. (Human mutation, 2024)
The genetic architecture of corneal endothelial dystrophies remains unknown in a substantial number of affected individuals. The proband investigated in the current study was diagnosed in the neonatal period with bilateral corneal opacification due to primary endothelial cell dysfunction. Neither his parents nor his sister had signs of corneal disease. Conventional karyotyping revealed a de novo translocation involving chromosomes 3 and 20, t(3;20)(q25;p11-12). Following genome and targeted Sanger sequencing analysis, the breakpoints were mapped at the nucleotide level. Notably, the breakpoint on chromosome 20 was identified to lie within the same topologically associated domain (TAD) as corneal endothelial dystrophy-associated gene OVOL2, and it is predicted to disrupt distal enhancers. The breakpoint at chromosome 3 is located within intron 2 of PFN2, which is currently not associated with any human disease. Further interrogation of the proband's genome failed to identify any additional potentially pathogenic variants in corneal endothelial dystrophy-associated genes. Disruption of a candidate cis-regulatory element and/or positional effects induced by translocation of OVOL2 to a novel genomic context may lead to an aberrant OVOL2 expression, a previously characterized disease mechanism of corneal endothelial dystrophy. Further research is necessary to explore how disruption of regulatory elements may elucidate genetically unsolved corneal endothelial dystrophies.
Keywords: dědičné dystrofie rohovky; Male; Female; Chromosomes, Human, Pair 3; Translocation, Genetic; translokace genetická; novorozenec; regulační oblasti nukleových kyselin; Pedigree; Transcription Factors; rodokmen; lidské chromozomy, pár 3; mužské pohlaví; ženské pohlaví; Corneal Dystrophies, Hereditary; transkripční faktory; Regulatory Sequences, Nucleic Acid; lidé; Humans; genetická predispozice k nemoci; Infant, Newborn; Genetic Predisposition to Disease